Apocalypse love [videorecording (Blu-ray)] - Vanguard, Vera; Lorigo, David; McGee, Bobby; Arroyo, Danny; Lang, Michael; Rowen, Jed; Fira, Hannah (Darkside Releasing, 2023)
When Tom lost his girlfriend BB to a tragic accident on prom night, the police suspected him, his family shunned him, and his friends blamed him or they would have, if he'd had any. Now he writes death metal love songs by BB's grave until his restless solitude is shattered when space aliens invade Earth and turn the dead into an army of zombie killers. Battling to save BB from becoming a puppet to alien masters and his desire to resurrect his lost love, Tom has to dodge bullets, legions of zombies, aliens, death rays, and a global apocalypse. This highly original festival-award-winning film is the first of its kind to feature the animation of puppets and hands in the same style that child-sized toy puppeteers have done in toy commercials over the past two decades.